Analysis of postural stability and body composition of women after unilateral mastectomy - Magdalena Kabała; Jacek Wilczyński; Katarzyna Grzanka (Kazimierz Wielki University, 2018)
Summary Introduction: The electrical bioimpedance method allows a non-invasive and precise assessment of the content of fat tissue, muscle mass or the amount of fluid in the body depending on the state of health or lifestyle. Changes in anthropometric features may affect postural stability, general physical fitness of women after mastectomy. In addition, changes in the distribution and amount of fat and lean body components may affect the ability to maintain balance. Aim of the study: Analysis of the relationship between postural stability and body composition of women after mastectomy based on posturographic examination. Material and methods: The study involved 40 women after mastectomy aged from 52 to 87 years. Postural Stability Test in static and dynamic mode on the Biodex Balance System platform was used to assess postural stability. The body bioimpedance method (BIA) was used to analyze the body composition. The research tool was the body composition analyzer Tanita MC 780 MA. The research was carried out in the Posturology Laboratory of the Institute of Physiotherapy at the Jan Kochanowski University in Kielce. Results and conclusions: Based on the research, a significant correlation was observed with a negative correlation in the Postural Stability Test, in static mode between fat mass and postural stability indexes. Also significant statistical results with a positive correlation were demonstrated in the same test between the total body water content and the postural stability indexes. Postural Stability Test in dynamic mode showed significant influence of lean and muscle mass in maintaining a stable posture. The standing posture of women after mastectomy was characterized by larger sublimations in the sagittal plane than the frontal plane (A / P> M // L).